2005
DOI: 10.1021/jp054187y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Reactivity of a New Ti-Containing Microporous/Mesoporous Material

Abstract: A new class of porous, mixed phase titanosilicate materials containing a microporous TS-1 phase and a mesoporous Ti-MCM-48 phase has been successfully synthesized. A novel, one-pot synthesis method was used in which the organic templates for the mesoporous and microporous phases were added sequentially to the same reaction mixture, followed by crystallization at 150 degrees C. The gemini surfactant 18-12-18 was used to form the Ti-MCM-48 mesophase; subsequent addition of tetrapropylammonium cation (TPA+) led t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 44 publications
(86 reference statements)
0
22
1
Order By: Relevance
“…We found that the catalytic activity for the oxidation of cyclohexene to be in the order, Interestingly, all catalysts showed exclusive and 100% selectivity for the formation of cyclohexene oxide, contrary to a previous report in which other products have been identified [38]. The turnover number (moles of cyclohexene converted/mol Ti) after 12 h of reaction at room temperature was estimated to be 59, 32 activity.…”
Section: Catalytic Studiescontrasting
confidence: 79%
See 2 more Smart Citations
“…We found that the catalytic activity for the oxidation of cyclohexene to be in the order, Interestingly, all catalysts showed exclusive and 100% selectivity for the formation of cyclohexene oxide, contrary to a previous report in which other products have been identified [38]. The turnover number (moles of cyclohexene converted/mol Ti) after 12 h of reaction at room temperature was estimated to be 59, 32 activity.…”
Section: Catalytic Studiescontrasting
confidence: 79%
“…Titania based MCM-48 materials have been utilized for selective oxidation of styrene [31], 2,6-di-tert-butylphenol [32,33], methyloleate [34], and cyclohexene [25,[35][36][37][38][39]. TiO2-MCM-48 prepared by a hydrothermal method was examined for the catalytic oxidation of cyclohexene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, NMR is widely used for studying the structure of intermediate species in solidification processes of nanozeolites, 1-3 external and internal surface active sites of porous nanomaterials, 4,5 atomic coordination and guest-host interactions in aluminosilicate, aluminophosphate, and mixed tetrahedral-octahedral porous materials. [6][7][8][9][10][11][12][13] Electron spin resonance (ESR) spectroscopy is based on the response of electron spins to microwaves under an external magnetic field. Its application is restricted to materials containing transition elements of low concentration.…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of highly active and stable catalysts under various operating conditions using tbutylhydroperoxide (TBHP) as oxidant has been reported [20][21][22].…”
Section: Introductionmentioning
confidence: 99%